Mutu Hedonik Mie Kering Labu Kuning Modifikasi Ikan Gabus Sebagai Makanan Darurat - Rachmawati, Yulia; Ramdany, Radeny; Rumoning, Siti Hadja (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2023)
Background: Papua and West Papua are categorized as regions in Indonesia with high seismicity. The most popular food in general is noodles. The content of β-carotene and fiber in noodles by adding pumpkin with cork fish modification in making dry noodles is expected to help meet food needs in disaster emergency situations. Objective: This research aims to determine the hedonic quality of color, aroma, taste, texture and overallquality of dry noodle products. Method: Experimental research design. The independent variables are dry noodles made from pumpkin modified by snakehead fish, hedonic quality. The panelists are totaling 30 people. Data processing uses SPSS 16.0. Results: Based on the results of the hedonic quality test using the hedonic method on the parameters of color, aroma, taste and texture of dried noodles, it can be seen from the whole that the treatment that was mostly chosen by panelists was in the P1 treatment with a scale of 4.0 with 50 grams of Pumpkin Porridge without cork fish. Conclusion: The hedonic quality of the three product formulations made obtained the most results chosen by panelists, namely the color of sample P1 totaling 26 people (86.7%) yellow criteria, P2 aroma totaling 11 people (36.7%) criteria not typical of pumpkin, P2 taste totaling 18 people (60.0%) criteria not sweet, P1 and P2 texture totaling 15 people (50.0%) chewy criteria, and P2 overall totaling 25 people (83.3%) good criteria.